Investigating Opportunities, Challenges, and Threats of Artificial Intelligence in Accounting Functions Using A systematic Literature Review - AYAD Meryem; EL MEZOUARI Said (African Scientific Journal, 2024)
Abstract Nowadays, Accounting one of the main functions in every company, is constantly developing due to several disruptive technologies such as Artificial Intelligence, this paper provides a systematic literature review to cover what opportunities Artificial Intelligence brings to the Accounting function, challenges as well as threats that Accounting is facing with the adoption of this technology, using Scopus as database, 30 research articles between 2010 and 2022, were selected, analyzed and synthesized. The results show that Artificial Intelligence technologies have great opportunities and are highly suitable for accounting activities. Further, improving cybersecurity by companies and the accounting workforce's ability are some of the main challenges. The unemployment crisis in the job market caused by artificial intelligence technologies poses a threat in the field of accounting. Keywords : Artificial intelligence ; Accounting ; Systematic Literature Review. Résumé De nos jours, la comptabilité, l'une des principales fonctions dans chaque entreprise, se développe constamment grâce à plusieurs technologies perturbatrices telles que l'Intelligence Artificielle. Cet article propose une revue systématique de la littérature pour couvrir les opportunités que l'Intelligence Artificielle apporte à la fonction comptable, ainsi que les défis et les menaces auxquels la comptabilité est confrontée avec l'adoption de cette technologie. En se basant sur Scopus comme base de données, 30 articles de recherche publiés entre 2010 et 2022 ont été sélectionnés, analysés et synthétisés. Les résultats montrent que les technologies d'Intelligence Artificielle offrent de grandes opportunités et sont particulièrement adaptées aux activités comptables. Cependant, l'amélioration de la cybersécurité par les entreprises et les compétences du personnel comptable représentent les principaux défis. La crise de l'emploi sur le marché du travail, due aux technologies d'Intelligence Artificielle, constitue une menace dans le domaine de la comptabilité. Mots clés : Intelligence Artificielle ; Comptabilité ; Revue de littérature systématique